Readings in labour economics and industrial relations - Shister, Joseph.( ed.) (Chicago, 1956)
SINCE THE original appearance of this volume, the pace of productive research in industrial relations has been little short of phenomenal. And for the most part, the writers have addressed themselves to the new and unresolved problems in the labor arena. For both these reasons, therefore, a revision was called for. The present edition, embodying twenty-three new selections, has benefited substantially from the suggestions by many of the teachers who used the first edition. But the basic framework of the book has been. kept intact.
Keywords: Industrial relations